(untitled) (Research, Society and Development, 2022)
Barium in only small concentrations is harmful to health and the environment, making it a challenge for water and effluent treatment processes, due to its complexity of removal and potential for contamination. The objective of this work is to carry out a literature review describing the physicochemical characteristics of barium, the traditional and emerging technologies used for its removal in water and effluent treatment processes. Therefore, the methodology used was a systematic review of the literature available in four databases: Scielo, CAPES, Science Direct and Google Scholar. Among the conventional techniques for the treatment of heavy metals, chemical precipitation, adsorption, ion exchange, coagulation, flocculation and flotation stand out. In terms of emerging technologies are the use of natural and synthetic products as adsorbents. With this work, it was verified the scarcity of methodologies for specific barium removal and the perspectives that open up for this field of research.